A development approach to industrial robots programming - Arnold, Gustavo V. (2003)
This paper proposes a development approach to industrial robot programming, that includes: a truly high level and declarative language; an easy-to-use frontend; an intermediate representation; an automatic generator of the robot code generators. So, we introduce a new paradigm to program industrial robots, that focus on the modeling of the system, rather than on the robot. It will improve the programming and maintenance tasks, allowing the reuse of source code, because this source code will be machine independent.